Valuation of Two Serological Tests in the Estimation of Rabies Virus Antibodies among Free-Ranging Vaccinated Dogs in Bengaluru, India - Das, Lekshmi J. (Innovations in Biological Science Vol. 4, 2024)
Rabies is a zoonotic viral disease caused by an RNA virus in the genus Lyssavirus of the family Rhabdoviridae. The disease is endemic in most African and Asian countries. Globally, rabies kills tens of thousands of people annually, and domestic dogs transmit most (99%) cases. Vaccination is the practical solution for the prevention of rabies in dogs. Assessment of the immunogenicity of vaccination includes estimation of specific rabies virus neutralizing antibodies (VNA) in the target species. We undertook a study to estimate the levels of VNA in free-roaming dogs with a history of rabies vaccination in Bengaluru city, India. We compared the rapid fluorescent focus inhibition test (RFFIT) and an in-house quantitative indirect ELISA (iELISA). The effectiveness of iELISA was evaluated using a two-tailed Spearman correlation analysis by comparing it with RFFIT. The study area comprised the jurisdiction of Bruhat Bengaluru Mahanagara Palike (BBMP), the Bengaluru civic body. The BBMP, along with several non-government organizations (NGOs), was conducting a trap-neuter-vaccinate-release program for the prevention of dog rabies. Serum samples were collected from 250 free-roaming dogs from representative regions of BBMP, of which 125 had a VNA titre of 0.5 IU or more by the RFFIT. Furthermore, 126 dogs showed percent positivity values (PP values) more than the cut-off PP value of 57.1 by the iELISA, accounting for 50.4% of satisfactory post-vaccinal serum conversion. The sensitivity and specificity of the ELISA was 94.4% and 95.2%, respectively. Based on these data, a quantitative ELISA may be a complementary tool for sero-monitoring immune responses of free-ranging animals after rabies vaccination. The study also recommends the need for enhanced rabies surveillance for the detection of rabies occurrence as a part of the National Action Plan for Rabies Elimination (NAPRE).